Pakistan's Sports Greats - Khalid Mahmood, Syed; Foreword by Mujahid, Chishty (Karachi Liliana International Publishers)
This books covers the shining stars of Bridge, Cricket, Hockey, Snooker and Squash.
Include Illustrations.
Keywords: Sports -- Pakistan -- Pakistani Sportsmen -- Pakistani Players -- Sports, Pakistan